ChemInform Abstract: Pd(II)‐Catalyzed Intramolecular Aminopalladation/Direct C—H Arylation under Aerobic Conditions: Synthesis of Pyrrolo[1, 2‐a]indoles. Issue 40 (12th September 2013) - Piou, Tiffany; Neuville, Luc; Zhu, Jieping
Abstract Optimized reaction conditions are established for the one‐pot bis‐cyclization of substrates (I) to produce pyrroloindoles in moderate yields.